Access to health services during the Colombian armed conflict: a challenge for the population with disabilities in the department of Meta - Nicolás Rodríguez Caicedo; Sebastián León-Giraldo; Catalina González-Uribe; Oscar Bernal (BMC, 2023)
Abstract Background The Colombian armed conflict has left millions of victims and has restricted access to different services provided by the government, especially for people with disabilities. This article studies the barriers faced by the victim population with disabilities when they want to access the health system in the department of Meta, Colombia, and offers a perspective from the experiences of people with disabilities who have been victims of the armed conflict in the country. Methods To carry out this qualitative study, focus groups were conducted to capture the experiences and feelings of this population in the context of violence and high conflict. Results The results show the barriers encountered by the victim population with disabilities, their families, and their caregivers when they want to access medical or health services. Conclusions Many problems affect the population with disabilities and the victim population in Colombia today. The Colombian government has not been able to establish adequate policies to eliminate or even reduce access to services such as health, education, housing, and social protection.